1997
DOI: 10.1038/sj.onc.1200858
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of human ribosomal protein L23A expression during cell growth inhibition by interferon-β

Abstract: Interferons inhibit cell growth in normal and tumorderived cells. The molecular basis of interferons antiproliferative activity remains to be de®ned. Using subtraction hybridization, a human melanoma dierentiation associated gene, mda-20, has been identi®ed that is down-regulated by treatment with interferon. Sequence analysis indicates that mda-20 is human ribosomal protein L23a (rp L23a). The mRNA levels of rp L23a and growth are diminished in a variety of human tumor cell lines following treatment with huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 28 publications
(38 reference statements)
5
28
0
Order By: Relevance
“…26,27,34,35 Among type I IFNs, IFN-␤ has potent antiproliferative activity against most human tumor cells in vitro in addition to its known immunomodulatory activities. [36][37][38][39][40] For these reasons, the availability of an animal model expressing IFN-␤ might help to understand the biological properties of this cyto- …”
Section: Discussionmentioning
confidence: 99%
“…26,27,34,35 Among type I IFNs, IFN-␤ has potent antiproliferative activity against most human tumor cells in vitro in addition to its known immunomodulatory activities. [36][37][38][39][40] For these reasons, the availability of an animal model expressing IFN-␤ might help to understand the biological properties of this cyto- …”
Section: Discussionmentioning
confidence: 99%
“…LDB1 is overexpressed in oral carcinoma (Mizunuma et al, 2003). Ribosomal proteins RPL8 (Tarantul et al, 2000), RPS13 (Denis et al, 1993), RPL5 (Frigerio et al, 1995), RPL23A (Jiang et al, 1997), RPL19 (Henry et al, 1993), RPL37 (Loging and Reisman, 1999), and RPS16 (Batra et al, 1991) are previously reported in association with multiple cancers other than NSCLC. Our data illustrate the success of our approach in discovering previously unidentified NSCLC-specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…If any or all of these genes are direct regulators of dierentiation, growth or the tumorigenic process then ectopically expressing these genes, using sense or inducible sense expression constructs (Jiang et al, 1995a(Jiang et al, ,c, 1996b(Jiang et al, , 1997, or blocking expression of these genes, using antisense or ribozyme based technologies (Alama et al, 1997;Su et al, 1998a), may directly modify these phenotypes in melanoma cells. Further studies designed to characterize the presently identi®ed DISH genes and to identify the remaining gene expression changes regulated as a function of induction of de®ned phenotypic changes in human melanoma cells are well warranted.…”
mentioning
confidence: 99%